Health system determinants of gestational diabetes mellitus screening of pregnant patients in public health facilities of district Jhansi: a cross sectional study - Sharma, Sudha; Malhotra, Anil K. (International Journal Of Community Medicine And Public Health, 2022)
Background: Worldwide, one in 10 pregnancies is associated with diabetes, 90% of which are gestational diabetes mellitus (GDM). Undiagnosed or inadequately treated GDM can lead to significant maternal and fetal complications. Due to this high prevalence, currently universal screening is being done for all pregnant women. The present study aims to assess the status of screening at these facilities and the factors which can improve this further. Methods: The status of screening was determined by GDM reporting format for last six months preceding the study from April 2018 to September 2018 and 100 auxiliary nurse midwives (ANMs) were selected from 4 blocks were interviewed to assess the factors and challenges which are associated with GDM screening with the help of a predesigned questionnaire. Results: Overall 40.05% (73.17-14.27%) antenatal women are being screened in Jhansi district at public health facilities. The percentage of screened women found positive for GDM were 4.71% (1.36-8.99%). The factors found to be associated with screening were factors like age, years of service and education, availability of logistics, distance of sub-center within 10 km of the Community Health Centre (CHC), having both Accredited Social Health Activist (ASHA) and Anganwadi worker (AWW) as motivators and doing screening at all sites (sub-center and out-reach). ANMs who had their own vehicle were found to do better screening. Conclusions: To make screening for GDM universal at all public health facilities continuous monitoring of sub-centers and VHNDs, support to ANMs in the form of availability of logistics, and involving the ASHA and AWW in routine screening are essential.